Periodic and aperiodic 3-D composite metastructures with ultrawide bandgap for vibration and noise control. (1st May 2022) - Muhammad; Lim, C.W.; Yaw, Zoe; Chen, Zhenyu
Graphical abstract: Highlights: Novel composite mechanical metastructure designs are proposed for low frequency broadband vibration and noise control. Ultrawide low frequency bandgap is reported by numerical wave dispersion study. Vibration attenuation over ultrawide bandgap region is demonstrated by numerical and experimental frequency response studies. An aperiodic design strategy is introduced to match the bandgaps of proposed metastructures. Both periodic and aperiodic metastructure arrangements demonstrated vibration attenuation over extremely wide frequency region. Abstract: Periodic composite structures as acoustic metamaterials have caught enormous research interest for the inherent peculiar dynamics characteristics, effective medium properties, and fantastic mechanical features to control vibration and noises at deep subwavelength scales. A 3-D composite metastructure design endowed with ultrawide three-dimensional bandgap is highly desirable for low frequency broadband vibration and noise control. In that context, the present study proposes two types of 3-D composite mechanical metastructure unit cell designs that are capable enough to induce low frequency ultrawide bandgaps by principle of mode separation. A 3-D polymeric casing is designed and spherical/cylindrical steel masses are embedded to enhance the dynamical characteristics and mechanical properties of the resonant systems. By a numerical study on wave dispersion, the presence of ultrawide bandgap and governing physical mechanism resulting in such broadband bandgap are discussed. An asymptotic parametric study is performed to investigate the effect of metastructure geometric parameters on the reported bandgaps. We performed numerical and experimental frequency response study on the periodic and aperiodic arrangements of the composite metastructures to envisage wave attenuation inside the bandgaps. Both periodic and aperiodic arrays of metastructures yield vibration attenuation over ultrawide frequency range that is promising for low frequency broadband vibration and noise control applications. The proposed composite metastructure design morphology and manufacturing/fabrication processes are also explained for practical design and applications. The proposed mechanical metastructure designs, our modelling technique, research methodology, and the reported findings may contribute to the design and application of metadevices where low frequency broadband vibration and noise control are desirable.